Surgical Metastasectomy for Visceral and Bone Prostate Cancer Metastases: A Mini-Review - Rajwa, Pawel; Yanagisawa, Takafumi; Gruber, Manuel; Heidenreich, Axel; Joniau, Steven; Briganti, Alberto; Shariat, Shahrokh F; Marra, Giancarlo; Gandaglia, Giorgio (European urology focus, 2023)
Despite growing interest in metastasis-directed therapy (MDT) for prostate cancer (PCa), little is known regarding the feasibility and effectiveness of surgical metastasectomy for isolated lesions. We performed a narrative review of the available evidence supporting metastasectomy for M1b-c lesions in men diagnosed with oligometastatic or oligorecurrent PCa. The case series and case reports we identified indicate that surgical MDT is a safe and feasible treatment option for well-selected patients with a small number of PCa metastases diagnosed via molecular imaging. It is difficult to draw evidence-based conclusions regarding the survival benefit of metastasectomy; however, metastasectomy might lead to a prostate-specific antigen response and could potentially delay systemic therapy in patients with oligometastatic PCa. Prospective studies incorporating novel imaging are needed to better establish the role of metastasectomy for patients with metastatic PCa. PATIENT SUMMARY: We reviewed the evidence on surgical removal of prostate cancer lesions that have spread to the organs (eg, liver and lung) or bone, which are called metastases. Limited results show that this approach is feasible and has favorable outcomes in selected patients.
Keywords: Metastasectomy; nádory prostaty; prospektivní studie; lidé; Humans; Prostatic Neoplasms; metastázektomie; Prospective Studies; radiochirurgie; Radiosurgery; prostatický specifický antigen; Prostate-Specific Antigen; Male; mužské pohlaví